Future of Remote Work and its implication on Organizational Structure (International Journal of Food and Nutritional Sciences, 2022)
The landscape of work is undergoing a transformative shift with the growing prevalence of farflung work. This review paper explores the drivers at the back of the adoption of far offpaintings, analyzes its blessings and demanding situations, and examines its profoundimplications on organizational systems